Reseña de Barcelona, A. (Ed.) (2000), Metaphor and Metonymy at the Crossroads. A cognitive perspective, New York, Mouton de Gruyter. - Miguel Ángel González Macías (Pragmalingüística)
Se trata de reseña de Barcelona, A. (Ed.) (2000), Metaphor and Metonymy at the Crossroads. A cognitive perspective, New York, Mouton de Gruyter.